Relative importance of soil properties and functional diversity to the spatial pattern of the forest soil nitrogen - Kang, Jian (2023)
Surface soil nitrogen (SN) is the main source of plant nutrient uptake, and its dynamic change is related to forest productivity, ecosystem carbon and nitrogen cycles, and water conservation. However, few studies have investigated the factors influencing SN. The linear mixing effect and generalized additivity model were used to investigate the spatial patterns and influencing factors of SN by collecting and measuring the total nitrogen content of forest soil samples in the middle and lower reaches of the Xijiang River Basin (XRB). We found that the total nitrogen content in broad-leaved forest soils was significantly higher than that in coniferous forest soils. Forest SN was influenced by soil properties and diversity indicators, and the full model constructed by influencing factors was more applicable to broad-leaved forests. Soil properties were the main explanatory factor for SN (53.53% in the full model, 61.02% in broad-leaved forests), with sub-surface soil nitrogen (sub SN) being the largest explanatory quantity factor (48.52% in the full model, 58.04% in broad-leaved forests). Therefore, forest management in the XRB should avoid damaging the sub-surface soils to prevent nitrogen loss. In the context of global change, the further study of the effect of nitrogen deposition on SN is warranted.